Problems Encountered In Modern Synchronous Machines - Xusanova Nigora Patxullayevna (Academia One, 2024)
This article examines rotor and stator faults and common problems of synchronous machines. We investigated major and minor faults and failures in synchronous and asynchronous machines (SAASM) to avoid redundant downtime, maintain quality of service, and minimize revenue losses for smart grid (SG) operators and planners. In addition, state-of-the-art fault detection, fault diagnosis, root causes of faults and troubleshooting measures for (a) transformers, (b) stators and (c) rotors are discussed. Our work provides a detailed taxonomy of rotor and stator faults, electrical and mechanical stress, and fault diagnosis schemes for stable SG operation. We believe that our research contribution is more versatile than previous works, covering all aspects of SAASM failures and malfunctions
Keywords: Transformer; stator and rotor; synchronous machines